Worksheet Based on Project-Based Learning in Science Learning in Elementary School - Angelina Aprillia Tupan; Marina Risa Marayate; Silomai Latuserimala; Marleny Leasa; John Rafafy Batlolona (LPPM Undiksha, 2024)
The underlying problem of this research is the lack of optimal application of teaching materials that can increase students' creativity and innovation, in accordance with 21st century skills. This study aims to test the practicality of Project-Based Learning (PjBL)-based worksheet design in science learning in elementary schools. The type of research used is development research using the 4-D model (Define, Design, Develop, Disseminate). The subject of this research involves design experts, material experts, technology experts, as well as teachers and students to test aspects of validity, practicality, and attractiveness. Data was collected through a non-test method in the form of a questionnaire that was quantitatively analyzed to evaluate product quality. The results of the study show that the average validation score of PjBL-based worksheets reaches 98%, indicating that this product is very valid. In addition, the results of the practicality test by teachers and students placed this worksheet in the very practical category. Based on these results, PjBL-based worksheets are declared feasible and effective to be used as teaching materials in elementary school learning. The implications of this study show that the development of PjBL-based teaching materials can be an innovative solution to improve the quality of learning in elementary schools.